Review Article: Pharmacological Activity of Robusta Coffee Plants (Coffee canephora) - Virginia, Jesica; Iqbal, Muhammad; Triyandi, Ramadhan; Andrifianie, Femmy (CV. Jasa Sukses Abadi, 2024)
Coffee canephora or robusta coffee is a tree-shaped cultivated plant belonging to the Rubiaceae family and the Coffea genus. This plant is most widely planted in Indonesia, namely 91% more than Arabica coffee plantations and has great potential in its use as an alternative treatment for various diseases. Robusta coffee contains flavonoids, alkaloids, tannins, saponins and polyphenols. The two main polyphenolic compounds found in coffee are chlorogenic acid and caffeine, which each account for about 90% of all phenols found in coffee. This review article aims to determine the various pharmacological activities found in robusta coffee obtained from experimental studies conducted using electronic databases in the form of Google Scholar, Pubmed, and Mendley. The inclusion criteria in the article search were articles in Indonesian and English published in the last 10 years and the exclusion criteria were articles that could not be accessed in full. The results of the study of 25 articles show that the robusta coffee plant in the seeds, leaves and fruit skin has antibacterial, antioxidant, anticancer, anti-inflammatory, antifungal, antidiabetic, and biolarvicide pharmacological activities.